Variation of bromine concentration as an essential trace element in human milk over lactation stages - Mohd Taufek, Nor Hidayah; Mohmad Sabere, Awis Sukarni; Mohamad Jamahari, Ummi Syahidah; Amran, Nur Balkhis; Fata Nahas, Abdul Rahman; Bidai, Joseph (IIUM Press, 2024)
Introduction: Bromine has been newly discovered in human milk but its importance in the growth and development of infants is unclear. Only a few studies have reported the concentration of bromine in human milk and considered it as an essential element, whereas others highlighted its toxicity of bromism in humans. This study aimed to determine the concentration of bromine as an essential trace element in human milk using a validated acid digestion method and discuss its variation over lactation stages. Method: Human milk samples were collected from three postpartum mothers and analysed using inductively coupled plasma mass-spectrometry (ICP-MS). The concentration of bromine was determined over a certain postpartum period, analysed using Microsoft Excel 2016,and reported descriptively. Results: Method validation parameters for bromine showed good linearity (R² > 0.999), limit of detection (0.003 μg/L), limit of quantification (0.01 μg/L), accuracy (96%), inter-day (3.76%RSD) and intra-day (3.35%RSD) repeatability. The median concentration of bromine in human milk decreased over six months of lactation, in μg/L: 1210, 674, 722, 671, 511 and 538. At later lactation months which were 12th, 13th, 14th, 15thand 21st, the median bromine concentration was in μg/L: 780, 815, 645, 846, 910, respectively. Conclusion: The acid digestion method by ICP-MS was robust and accurate in determining bromine concentration in human milk. The consistent variation of bromine in human milk over lactation stages may indicate its importance in supporting infant development in the first two years of age. Future research should explore the role of bromine in infants’ development, its chronobiological importance, and the risk of deficiency or toxicity.